The Role of Transformational Leadership in Improving Teacher Motivation at SMP Muhammadiyah 7 Medan - Maysarah, Nur Siti; Fadhli, Muhammad (JMSP (Jurnal Manajemen dan Supervisi Pendidikan), 2024)
Abstract: This study was conducted with the aim of determining the role of transformational leadership in improving teacher motivation at SMP Mohammadieh 7 in Madan. The research method used was qualitative and focused on accurate descriptions of events in the field. Data collection was carried out through library and field research using interviews, observations and documents. The results of the study showed that transformational leadership implemented by the principal had quite significant changes in teacher motivation and created a supportive and positive work environment where teachers felt important and motivated to participate effectively. By showing appreciation regularly, managers can create a cohesive vision and inspire their employees. This improves the quality of teaching and learning and affects student performance. In addition, this approach is effective in overcoming resistance to change through open communication and effective conflict management. Finally, change Teachers feel more motivated because they see themselves as an important part of the larger school vision at SMP Mohammadiyeh 7 Madan. This plays an important role in improving teacher motivation and the overall quality of education and shows the need for personal leadership to achieve better educational goals, motivate and involve something together.Keywords: Role of Leadership, Transformational Leadership, Teacher Motivation